Preliminary exploration of the ability of HUC-MSCs to restore the lung microbiota and related metabolite disorders in IPF treatment: combining 16S sequencing and metabolite analysis - Zhou, Shuang; Luo, Yukai; Liu, Jun; Huang, Jishui; Zhang, Xiaojing; Jia, Qing-chun; Lin, Yijian; Huang, Zhenyong; Zeng, Yiming; Cheng, Wenzhao (Frontiers in Microbiology, 2025)
BackgroundIdiopathic pulmonary fibrosis (IPF) is a chronic and progressive pulmonary disease, and effective therapies to reverse the natural course of IPF are lacking. A growing number of studies have shown that the use of human umbilical cord-derived mesenchymal stem cells (HUC-MSCs) is a promising therapeutic strategy. However, the mechanism by which HUC-MSCs alleviate IPF and how HUC-MSCs affect the lung microbiota are still unclear and need further exploration.MethodsBleomycin (BLM) injection was used to establish a mouse model of IPF, and 16S rDNA sequencing and LC–MS/MS metabolomics were performed to explore the underlying mechanism of HUC-MSCs as IPF treatment. Thirty mice were allocated into three groups, namely, the Control, BLM, and BLM + HUC-MSCs groups, and lung morphology; levels of α-SMA, FN1 and COL1A1; and levels of the inflammatory cytokines TNF-α, IL-1β, IL-6, and TGF-β1 were evaluated. Bronchoalveolar lavage fluid (BALF) samples from six mice in each of the three groups were collected randomly for 16S rDNA sequencing to analyze the lung microbiota and untargeted metabolomics analysis.ResultsHuman umbilical cord-derived mesenchymal stem cells restored alveolar morphology and reduced the expression of α-SMA, FN1 and COL1A1 and the inflammatory cytokines TNF-α, IL-1β, IL-6, and TGF-β1 in IPF model mice, confirming the anti-inflammatory properties of HUC-MSCs in IPF treatment. The 16S rDNA sequencing results indicated that HUC-MSCs treatment effectively decreased α diversity indices, such as the Abundance-based Coverage Estimator (ACE) and Shannon indices, as well as β diversity, leading to a decrease in microbiota abundance. The metabolomics analysis revealed that the metabolites exhibiting notable differences included primarily organic acids and their derivatives, lipids and lipid-like molecules, phenylpropanoids and polyketides, and organic nitrogen compounds, indicating the potential of HUC-MSCs to exert antifibrotic effects through these metabolic pathways.ConclusionOverall, our study preliminarily confirmed that IPF in mice was closely related to microbial and metabolic dysbiosis. In mice with IPF, treatment with HUC-MSCs modulated dysregulated metabolic pathways and improved microbiota function to a state more comparable to that of the Control group. This study provides new insights into the potential mechanisms and treatments of IPF.